Montagem de novo e análise dos transcriptomas de duas espécies neotropicais de Cyphoderus Nicolet, 1842 (Collembola: Paronellidae: Cyphoderinae) - Brito, Nathan Paiva (2020)
Considered one of the most abundant organisms in the edaphic fauna, the Collemsa act in the process of nutrient cycling and therefore have a great affinity with this environment. Due to this affinity, changes in soil environments quickly affect Collembola populations, changing their population dynamics caused by physiological stress. Such environmental changes can be observed at genetic levels, and biological and evolutionary processes can be studied through approaches that evaluate the expression of genes. The study of gene expression simultaneously enables the understanding of the structure of the transcripts, allele information, as well as some techniques that make it possible to verify the abundance of transcripts and their isoforms, in addition to providing a high resolution of the expression. In this work, we use RNA-seq technology to sequence through the Illumina platform and assemble the set of transcripts from two species of the genus Cyphoderus from different regions using the Trinity Software. C. similis presented the number of transcripts (46,269) compared to other Collembola species already studied. C. innominatus had a high number of transcripts (60,002), despite being still below the maximum number of transcripts described for Collembola. EvidentiaGene was a key program to produce better quality transcriptomes in the analyzes. The ExN90 statistics (~ 3 kb in C. similis and ~ 2.5 kb in C. innominatus) were more representative of the transcriptomes than the N50 statistics generated by Trinity (~ 2.1 kb in C. similis and ~ 1.5 kb in C. innominatus). The functional annotation detected 2,082 and 1,252 more genes for C. similis and C innominatus respectively, proving to be an important tool. 2,753 and 10,850 identifiers shared in both species were identified through Pfam and gene ontology respectively, in addition to 640 and 1,319 unique GO identifiers and 95 and 106 exclusive Pfam identifiers for C. similis and C. innominatus respectively. This work is the first description of partial transcriptome sequencing data in species of the Cyphoderus genus, providing a resource of genetic information necessary for the accurate understanding of the biology of the Cyphoderus genus and consequently about Collembola, providing a bias in the creation of questions and answers about the origin and evolution of important characteristics of these animals.